DIAGNOSTIC CAPABILITIES OF ULTRASOUND DIAGNOSTICS OF LUNG CHANGES IN THE CAUSATIVE AGENT OF CORONAVIRUS INFECTION COMPARED TO CT - ISMAILOVA M. KH; ZHONIBEKOV ZH. ZH. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The" gold standard" of SARSCoV-2 diagnostics is the detection of viral RNA in a nasopharyngeal smear using PCR. In the diagnosis of COVID-19, the sensitivity of CT is 98%, which was significantly higher than the sensitivity of PCR-71%. Ultrasound of the lungs demonstrates a high diagnostic value in the assessment of various lung diseases and is superior in sensitivity and specificity to X-ray examination of the chest organs.